2003
DOI: 10.1093/intqhc/mzg036
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with primary health care services in the United Arab Emirates

Abstract: The significantly higher patient satisfaction in the RIC compared with the RTC was a strong a priori expectation, suggesting that this satisfaction questionnaire is a useful quality assurance tool in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
73
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 16 publications
15
73
1
5
Order By: Relevance
“…Similarly Hayati et al (2010) did not find any significant differences in patient satisfaction based on patients' nationality 13 . In contrast to our findings, Al-Qahtani et al (2012), Hayati et al (2010) and Margolis et al (2003) showed that level of satisfaction in some aspects was higher for patients with specific sociodemographic variables such as educational level and economic status 13,19,24 . Similar to the literature results verified significant association between patient satisfaction, hospital type and patients' length of stay, whereas other hospital's characteristics did not reveal any significant relation 13,26 .…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly Hayati et al (2010) did not find any significant differences in patient satisfaction based on patients' nationality 13 . In contrast to our findings, Al-Qahtani et al (2012), Hayati et al (2010) and Margolis et al (2003) showed that level of satisfaction in some aspects was higher for patients with specific sociodemographic variables such as educational level and economic status 13,19,24 . Similar to the literature results verified significant association between patient satisfaction, hospital type and patients' length of stay, whereas other hospital's characteristics did not reveal any significant relation 13,26 .…”
Section: Discussioncontrasting
confidence: 99%
“…received printed educational materials at some point. Low rates of The Patient satisfaction questionnaire was constructed based on previously used questionnaire from the literature dealing with the benefits of health educational services and patient satisfaction [18][19][20][21][22][23][24][25]. The questionnaire was pre-tested with 5% (less than 20%) of the sample size, using other clinics with similar features in order to avoid repeated enrolment of the same participant.…”
Section: Resultsmentioning
confidence: 99%
“…There was more satisfaction in hospitals located in smaller areas. However, studies carried out in Sri Lanka (Senarath et al, 2006), China (Hansen et al, 2008) and the United Arab Emirates (Margolis et al, 2003) suggests that patients who were admitted to hospitals in urban areas showed higher satisfaction.…”
Section: Socio-economic Statusmentioning
confidence: 98%
“…Investigations in the United Arab Emirates (Margolis et al, 2003) and Saudi Arabia (Al-Doghaither, 2004) showed that patients who have a university degree are less satisfied than other patients. All other studies did not show such a relationship between education and satisfaction with health care centers.…”
Section: Literacymentioning
confidence: 99%